'Through my eyes': feminist self-portraits of Osteogenesis Imperfecta as arts-based knowledge translation. Issue 4 (8th August 2022) - Macdonald, Diane; Van Gijn-Grosvenor, Evianne L.; Montgomery, Melinda; Dew, Angela; Boydell, Katherine
Abstract : In this paper, we present an exploration of arts-based knowledge translation through photography highlighting the lived experience of Osteogenesis Imperfecta (OI), a genetic disorder. It forms part of our larger photovoice research project that involved six female photographers with physical impairment. This group of women shared their personal experiences through photographic stories to challenge pervasive, limiting negative attitudes and assumptions that surround disability. In this paper, we focus on the data, analysis and discussion to one type of impairment, OI, and two photographers' work to present their: embodied expertise and knowledge of living with OI ; self-portraits as contemporary disability identity, contributing to intersectionality in feminist and disability arenas ; authentic voice as co-authors of this paper using Drew and Guillemin's interpretive engagement framework ; original arts-based research insights currently absent in the meagre qualitative research on OI . By presenting, analysing and interpreting self-portraits of OI as valuable arts-based knowledge, we hope to provide readers with a better understanding of disability and femininity as a pathway to greater inclusion.